Quantification of unfractionated heparin in human plasma and whole blood by means of novel fluorogenic anti-FXa assays - O'DONNELL, JAMES (Elsevier, 2011)
Novel and sensitive plate-based fluorogenic anti-factor Xa (FXa) assays were investigated to quantify unfractionated heparin (UFH) in human plasma and whole blood within the therapeutic ranges of 0-1.6 U/mL and 0?0.8 U/mL, respectively. Two fluorogenic anti-FXa assay methods were defined for low (0-0.6 U/mL) and high (0.6-1.2 U/mL) pharmacologically relevant UFH concentration ranges in pooled human plasma. In both cases significant differences were observed at intervals of 0.2 U/mL (P < 0.05). The semi-logarithmic plots of the calibration curves in the low and high UFH range were both fitted to linear regressions with correlation coefficients of 0.96 and >0.99, respectively. The assay was also optimized for whole blood which was capable of differentiating UFH concentrations at intervals of 0.2 U/mL (P < 0.05) in the range of 0-0.4 U/mL. The statistically different results were fitted to a linear regression with a correlation coefficient of >0.99. The results obtained in this study could assist diagnostic laboratories towards improved monitoring of UFH therapy.
PUBLISHED
Keywords: Hematology; human plasma